Monosomy of distal 4q does not cause facioscapulohumeral muscular dystrophy. Issue 5 (May 1996) - Tupler, R; Berardinelli, A; Barbierato, L; Frants, R; Hewitt, J E; Lanzi, G; Maraschio, P; Tiepolo, L
Abstract : Facioscapulohumeral muscular dystrophy (FSHD) is a hereditary neuromuscular disorder transmitted in an autosomal dominant fashion. FSHD has been located by linkage analysis in the most distal part of chromosome 4q. The disease is associated with deletions within a 3.2 kb tandem repeat sequence, D4Z4. We have studied a family in which an abnormal chromosome 4 segregates through three generations in phenotypically normal subjects. This chromosome is the derivative of a (4;D or G) (q35;p12) translocation. Molecular analysis of the region 4q35 showed the absence of the segment ranging from the telomere to locus D4F104S1. Probe p13E-11 (D4F104S1), which detects polymorphic EcoRI fragments containing D4Z4, in Southern blot analysis showed only one allele in the carriers of the abnormal chromosome 4. Probe p13E-11 EcoRI fragments are contained in the subtelomeric region of 4q and their rearrangements associated with FSHD suggested that the gene responsible for the muscular dystrophy could be subject to a position effect variegation (PEV) because of its proximity to subtelomeric heterochromatin. The absence of the 4q telomeric region in our phenotypically normal cases indicates that haploinsufficiency of the region containing D4Z4 does not cause FSHD.